THE EFFECT OF WORK MOTIVATION AND WORKLOAD ON EMPLOYEE PERFORMANCE IN PT. PLN (PERSERO) UPT PADANG - Aminar Sutra Dewi; Darniscaya Waruwu (LP2M Universitas Bina Bangsa, 2023)
This study aims to determine the effect of work motivation on employee performance and the effect of workload on employee performance at PT. PLN (Persero) UPT Padang. This research is a type of quantitative research with a survey approach chosen because it uses a questionnaire as a research instrument. The research object is PT. PLN (UPT persero Padang. The research sample used saturated sampling of 52 samples, using multiple linear regression analysis. The results showed that partially work motivation had a negative and significant effect on employee performance and workload had a negative and significant effect on employee performance. employees at PT.PLN (Persero) UPT Padang.